Nukleosinteza po velikem poku - Štoka Sedmak, Leonard (Matrika, 2022)
Big Bang nucleosynthesis describes the production of light nuclei - 2H, 3He, 4He and 7Li - from neutrons and protons during the early phases of the Universe. The article first describes the theory of the formation of these nuclei, followed by predictions of their mass fractions, which are derived from a mathematical description of the topic, and finally a comparison of these with the latest measurements in this field, as well as establishing the validity of the described theory.
Keywords: Big Bang; cosmology; kozmologija; nucleosynthesis; nukleosinteza; veliki pok